2011
DOI: 10.1016/j.bbamem.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxycholesterols on thermo-induced membrane dynamics

Abstract: The effect of temperature change(s) on the dynamics of giant unilamellar vesicles containing oxidized and non-oxidized cholesterol was investigated and characterized. We have demonstrated that (i) major cholesterol auto-oxidation products, 7β-hydroxycholesterol (7β) and 7-ketocholesterol (7keto), rendered vesicles more responsive to temperature changes; (ii) 7keto imparted greater thermo-induced membrane dynamics than 7β; (iii) 7β and 7keto vesicles synergistically were more thermo-responsive than the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…In fact, it has been reported that oxidized cholesterol (OxyCHOL) renders membranes unstable more than non-oxidized cholesterol-containing systems [3,4]. In a recent study, we investigated the thermo-responsiveness of OxyCHOL in lipid vesicles [5]. We observed changes in membrane perturbation and we proposed a mechanism behind the change in stability.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In fact, it has been reported that oxidized cholesterol (OxyCHOL) renders membranes unstable more than non-oxidized cholesterol-containing systems [3,4]. In a recent study, we investigated the thermo-responsiveness of OxyCHOL in lipid vesicles [5]. We observed changes in membrane perturbation and we proposed a mechanism behind the change in stability.…”
Section: Introductionmentioning
confidence: 91%
“…We had reported that 7KC was one of major derivatives of cholesterol after oxidative stress [5]. It has been reported that this OxyCHOL is related to crystal formation on macrophages and even muscles [27].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations